Assessment of breast cancer literacy among female students in a Pakistani university - Murtaza, Ghulam; Abbasi, Sadaf Imtiaz; Irum, Hina; Jadoon, Mehreen Khan; Hussain, Izhar (Contemporary Oncology/Współczesna Onkologia, 2011)
Background: Today, after lung cancer, breast cancer is the second main cause of death in women worldwide. Amongst Pakistani women of all literary groups as well as in women of all age groups, the most common cancer is breast cancer. Objective : The primary objective of this study was to assess the complete information about breast cancer, its signs, indications, an orderly process and understanding about the management of this disease in female students in a Pakistani university. Material and methods: This questionnaire-based survey study was carried out during February-April, 2011 at COMSATS Institute of Information Technology (CIIT), Abbottabad, Pakistan. Five hundred of university students of twelve different departments were asked to fill out a questionnaire by students of pharmacy along with an experienced pharmacist faculty member. Participants were asked 27 questions on the awareness of breast cancer and six questions were asked which were related to their attention about breast cancer and its management. Results : Mean age of the participant students was 21.5 years. It was evident from the results that a large number of students did not have sufficient knowledge, or had no awareness of breast cancer. Regardless of extensive international and national public education programmes, more than 66% of the female students at CIIT were aware of breast cancer, and its examination and screening practices such as breast self-examination and clinical breast recommendations. The students also reported that their family physicians had never motivated them to have clinical breast examinations. Conclusion : This study emphasized the urgent need to arrange a breast cancer awareness crusade in CIIT, and other institutes as well, highlighting the symptoms, diagnosis and management of breast cancer. Since Pakistani females do not generally connect to the screening practices, nurses and female health visitors should jointly instruct women on the potential for early finding of cancer using a suitable screening tool such as the breast self-examination.